Alpha Synuclein Connects the Gut-Brain Axis in Parkinson’s Disease Patients – A View on Clinical Aspects, Cellular Pathology and Analytical Methodology - Schaeffer, Eva; Kluge, Annika; Böttner, Martina; Zunke, Friederike; Cossais, Francois; Berg, Daniela; Arnold, Philipp (Frontiers in Cell and Developmental Biology, 2020)
Parkinson’s disease (PD) is marked by different kinds of pathological features, one hallmark is the aggregation of α-synuclein (aSyn). The development of aSyn pathology in the substantia nigra is associated to the manifestation of motor deficits at the time of diagnosis. However, most of the patients suffer additionally from non-motor symptoms, which may occur already in the prodromal phase of the disease years before PD is diagnosed. Many of these symptoms manifest in the gastrointestinal system (GIT) and some data suggest a potential link to the occurrence of pathological aSyn forms within the GIT. These clinical and pathological findings lead to the idea of a gut-brain route of aSyn pathology in PD. The identification of pathological aSyn in the intestinal system, e.g. by GIT biopsies, is therefore of highest interest for early diagnosis and early intervention in the phase of formation and propagation of aSyn. However, reliable methods to discrimination between physiological and pathological forms of enteral aSyn on the cellular and biochemical level are still missing. Moreover, a better understanding of the physiological function of aSyn within the GIT as well as its structure and pathological aggregation pathways are crucial to understand its role within the enteric nervous system and its spreading from the gut to the brain. In this review, we summarize clinical manifestations of PD in the GIT, and discuss biochemical findings from enteral biopsies. The relevance of pathological aSyn forms, their connection to the gut-brain axis and new developments to identify pathologic forms of aSyn by structural features are critically reviewed.